Implementation Of Corporate Law Norms: Analysis Of The Element Of The No Losses To The State As An Announcement Of Corporate Criminal By State-Owned Enterprises (Journal of Namibian Studies : History Politics Culture, 2023)
State-Owned Enterprises (SOEs) are recognized as one of the most important factors driving economic activities, and manage a very large amount of state finances, thus making the SOE environment vulnerable and frequent criminal acts, especially corruption/bribery. Law enforcement against criminal acts within SOEs is generally charged to directors or other leadership officials, not yet touching SOEs Corporations. This research uses normative juridical research methods that are descriptive prescriptive, using data and information from various literature sources which are then selected and classified based on useful material and are very relevant tothe focus of this research. This study found indication  of the inability of law enforcers to punish  SOEs, because there is a strong perception that there is no State loss in cases involving SOEs, although based on the calculation of authorized agencies, it can be seen that there are real losses of SOEs. The absence of this element of State loss arises based on the set-off approach between the expenditure of fine costs (if convicted by the Court) by the treasury of SOEs and the receipt of these fine costs by the State treasury. Because there is no loss to the State, there is no unlawful act by SOEs. This research  is important to be carried out with the aim of providing a different perspective, although there is a set-off approach, but in terms of criminal law norms, SOEs as legal entity, are legal subjects (rechts persoon) besides humans (naturlijk persoon), which have the same rights and obligations as humans. Thus, it is feasible and can be charged with criminal liability, if it violates the legal norms stipulated in the Criminal Law applicable to the Corporation, through proving the elements of criminal acts  and by applying Identification Theory, Imputation Theory and other corporate theories.